Good education : the virtues of learning - Pritchard, Ivor A.; Council for Basic Education (Norwalk, CT : United Publishers Group, 1998)
A guide for teachers and parents which offers advice on how to develop educational programs to foster the four moral virtues of friendship, honesty, courage, and justice in children.
"CBE, Council for Basic Education.".
Includes bibliographical references (p. [249]-256).
Adult
Keywords: Moral education; Moral education